Paclitaxel and carboplatin in the treatment of advanced or recurrent endometrial cancer: a large retrospective study. Issue 1 (1st January 2007) - Sovak, M. A.; Dupont, J.; Hensley, M. L.; Ishill, N.; Gerst, S.; Abu-Rustum, N.; Anderson, S.; Barakat, R.; Konner, J.; Poyner, E.; Sabbatini, P.; Spriggs, D. R.; et al.
Abstract : The aim of this study was to assess the efficacy and tolerability of paclitaxel and carboplatin (TC) in the treatment of patients with advanced or recurrent endometrial cancer. Patients eligible for this retrospective analysis had endometrial cancer with either advanced or recurrent measurable disease (untreated primary stage III/IV or stage III/IV patients with persistent, measurable disease [≥2 cm] after surgery), Eastern Cooperative Oncology Group (ECOG) performance status ≥3, and received at least one cycle of TC. Response rates were determined using Response Evaluation Criteria in Solid Tumors criteria. Institutional Review Board approval was obtained prior to the initiation of this study. Eighty-five eligible patients, with a median age of 62 years (range 36–80) were identified. Fifty-seven (67%) of patients were treated at the time of recurrence. Prior radiation therapy had been used in the treatment of 36 (42%) patients, while 13 (15%) patients had received prior chemotherapy. Median follow-up time was 11.7 months (range 1.1–96.7 months), and the median number of cycles of therapy received was six (range 1–18). The overall response rate (ORR) was 43%, with a complete response rate of 5% and a partial response rate of 38%. Chemotherapy-naive patients had an ORR of 47%. Only seven (8%) patients had to discontinue therapy due to toxicity. Median progression-free survival was 5.3 months (95% CI, 4.6–7.4), with a median overall survival of 13.2 months (95% CI, 11.7–18.2). We conclude that TC is an active and tolerable regimen in the treatment of patients with advanced or recurrent endometrial cancer